Positive Contribution of Extensive Reading to EFL Students’ Learning - Nur Hasanah Safei; Fitri Rini Ekasari (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This qualitative study investigates the positive contribution of extensive reading to EFL Students’ learning. The data were collected through students’ reflection. The participants of this study were a class majoring in English Education Department at one of Islamic higher education in South Sulawesi. The findings reveal that students got some positive contribution of extensive reading to students’ learning. There are three positive contribution found in this study, those are creating and sustaining students’ motivation to read more, helping students in developing a wide vocabulary and improving students’ reading comprehension. Based on the findings, it is expected to contribute to the teaching of English especially in the use extensive reading technique in teaching reading. However, in order to get maximum the positive contribution of extensive reading, it is suggested that some aspects of the technique should be improved; these include the improvement of teacher’s understanding of the principles and concepts of extensive reading, the insight of the importance of giving clear instructions, and the awareness of designing various activities. Positive Contribution of Extensive Reading to EFL Students’ Learning